Dissipative Controller Design for Networked Control Systems via the Markovian Jump System Approach - Asep Najmurrokhman; Bambang Riyanto T.; Arief Syaichu-Rohman; H. Hendrawan (Journal of Engineering and Technological Sciences, 2013)
This paper describes a dissipative controller design for networked control systems modeled by the Markovian jump system. Dissipativity refers to the existence of a supply rate dealing with the system such that the closed-loop system has a dissipative property. The main result of this paper is a solvability condition in terms of linear matrix inequalities for achieving dissipativity of a dynamic output feedback problem in networked control systems via the Markovian jump system approach. A numerical example is given to show the efficacy of the proposed design.